1995
DOI: 10.1002/jmv.1890450417
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies that block virus attachment to vero cells are a major component of the human neutralizing antibody response against dengue virus type 2

Abstract: Epidemiological data strongly implicate a role for the host humoral immune response in both protection against and exacerbation of dengue virus-caused disease. In an effort to characterize elements of the normal human immune response against dengue virus we have addressed the issue of antibody-mediated neutralization of dengue virus. We show here the ability of both mouse monoclonal antibody 3H5 and human anti-dengue neutralizing sera to block binding of dengue-2 virus to monkey kidney (Vero) cells. Since Vero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
58
1
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(62 citation statements)
references
References 44 publications
2
58
1
1
Order By: Relevance
“…In our experiments, the levels of secreted prM were high relative to intracellular prM levels, both from virally infected C6/36 cells and from pSVprM-E-transfected COS cells, suggesting that prM processing was impaired. Similarly, infectious DENV particles with a high proportion of prM have consistently been found to be released from infected cells (Anderson et al, 1997;He et al, 1995;Henchal et al, 1985;Murray et al, 1993;Putnak et al, 1996;Randolph & Stollar, 1990;Roehrig et al, 1998;Wang et al, 1999). Recent studies mutating the prM furin cleavage site of TBEV (Elshuber et al, 2003) and DENV-2 (Keelapang et al, 2004) have shown that, whilst cleavage of prM is essential for virus infectivity, enhanced furin cleavage of the DENV prM protein affects virus export adversely, suggesting that it may be advantageous for DENV to retain some prM on the virus surface.…”
Section: Discussionmentioning
confidence: 96%
“…In our experiments, the levels of secreted prM were high relative to intracellular prM levels, both from virally infected C6/36 cells and from pSVprM-E-transfected COS cells, suggesting that prM processing was impaired. Similarly, infectious DENV particles with a high proportion of prM have consistently been found to be released from infected cells (Anderson et al, 1997;He et al, 1995;Henchal et al, 1985;Murray et al, 1993;Putnak et al, 1996;Randolph & Stollar, 1990;Roehrig et al, 1998;Wang et al, 1999). Recent studies mutating the prM furin cleavage site of TBEV (Elshuber et al, 2003) and DENV-2 (Keelapang et al, 2004) have shown that, whilst cleavage of prM is essential for virus infectivity, enhanced furin cleavage of the DENV prM protein affects virus export adversely, suggesting that it may be advantageous for DENV to retain some prM on the virus surface.…”
Section: Discussionmentioning
confidence: 96%
“…4). Blocking of cell surface attachment or receptor engagement through steric hindrance may be a common mechanism and has been suggested to explain the activity of DENVimmune sera (176). However, many antibodies are also capable of blocking infection at a postattachment step (51,59,167,(177)(178)(179).…”
Section: Mechanisms Of Neutralizationmentioning
confidence: 99%
“…Prevention of viral infection by antibodies depends on diverse mechanisms such as prevention of viral attachment to the host cell (1,2), activation of the complement system (3,4), opsonization (5), antibody-dependent cell-mediated cytotoxicity (6,7), and inhibition of the release of daughter viruses from infected cells (8)(9)(10). Such a wide variety of antibody activities are mediated by a generation of various classes of antibody (IgG, IgA, and IgE) besides IgM and IgD through class switch recombination (CSR; 11).…”
Section: Introductionmentioning
confidence: 99%